A Latin-Amerikába kivándorolt magyarság demográfiai helyzete - Szondi Ildikó; Baranyi Emese Zsuzsanna; Mészáros János; Szabó Henriette Éva (Szegedi Tudományegyetem Állam- és Jogtudományi Karának tudományos bizottsága Szeged, 2009)
Migration always played an important role in the Hungarian population tendencies, not just in numbers but culturally too. There were Hungarians in the conquest of the New World, and Latin America housed important waves of migration time by time for political and economical reasons, especially in the second decade of the XX. century. The first wave occurred in the beginning of the 1920s after the break of the AustroHungarian Monarchy, the second in the middle of the 1920s due to the political fear of the Horty-system, and the third wave happened by the end of the decade as part of the Economic Crash. Yet, there were other smaller movements until the 1960s, especially to Brazil, Uruguay and Argentina where until today there are significant Hungarian colonies. Their assimilation processes were slow, but progressive, thought there were always interests aimed to maintain the Hungarian identity.
Keywords: Társadalomtudományok; Szociológia